The Effect of Social Media and Sports Technology Exposure on Anxiety among late adolescent athletes - Ramdan Pelana; Yuliasih; Syukur Dharmawan; Jhoni Triyanto; Sri Sundari (Jurnal Segar, 2026)
The purpose of this study was to determine the level of anxiety among late adolescent athletes based on gender and sports category. The method used in this study is research Cross-sectional research is a type of research design in which you collect data from many different individuals at a single point in time. The population of this study was 135 people and 101 samples were obtained using accidental sampling techniques. The survey data collected, was entered into the IBM SPSS 25 tool for analysis statistics with ANOVA two-way. As a result of this study, the anxiety data for males’ totaling 64 respondents, the average age is 19.67 years, and the average anxiety level is 66.84 ± 6.47. Of the four sports categories, the order of anxiety levels from highest to lowest is the measured sports category at 69.40%; the martial arts category at 65.80%; the game sports category at 68.68%, and the lowest was in the accuracy sports category at 65.14%. and females’ there are 37 respondents with an average age of 19.08 years, with an average anxiety level of 65.35 ± 7.06. Of the four sports categories, the order of anxiety levels from highest to lowest is the measured sports category at 671.80; the martial category at 65.60%; the game sports category at 65.43%, and the lowest was in the accuracy sports category at 62.69%. Males’ anxiety levels in the accuracy, martial, and game sports categories are higher than females. However, it is inversely proportional to the category of measured sports which is that females’ anxiety levels are higher than males. Anxiety levels between categories did not differ significantly except that in the accuracy exercise category with the measured sports category there was a significant difference (p-value <0.05), in both males and females.